2020
DOI: 10.1016/j.acap.2020.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Development of K-12 Educational Resources During the COVID-19 Pandemic

Abstract: need for guidance from the medical community about COVID-19 by engaging medical students as leaders in sharing knowledge about COVID-19 with the general public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…8 Reardon et al described how students created a virtual COVID-19 classroom to teach school-aged children ageappropriate and accurate information about the pandemic. 9 Both showcase the impact of tapping into students' experience and skill with social media to develop future pediatric advocates, more critical now, post-COVID-19, than ever.…”
Section: T a G G E D H 2 Students As Agents Of Changet A G G E D E N Dmentioning
confidence: 99%
“…8 Reardon et al described how students created a virtual COVID-19 classroom to teach school-aged children ageappropriate and accurate information about the pandemic. 9 Both showcase the impact of tapping into students' experience and skill with social media to develop future pediatric advocates, more critical now, post-COVID-19, than ever.…”
Section: T a G G E D H 2 Students As Agents Of Changet A G G E D E N Dmentioning
confidence: 99%
“…(2020) analyzed the NYC Metro Area School Counseling Center Website ( n = 138) and found that half of the schools provided information about distance counseling. Reardon et al. (2020) developed a COVID-19 classroom website for K-12 students to help them develop appropriate education, resiliency, and effective communication leading to an understanding of the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ademais, a pandemia causada pelo novo coronavírus COVID-19 foi responsável por grandes mudanças, ocasionando alterações na forma de ensino do curso superior, a exemplo da educação médica que necessitou suspender as atividades presenciais e estágios práticos, passando a adotar um ensino híbrido ou um ensino a distância e avaliações on-line para os discentes do curso de medicina (Reardon et al, 2020). A inserção ao EAD (ensino a distância) em um curso 100% presencial, a dificuldade em se concentrar, a preocupação com o acúmulo de matérias e o possível atraso do semestre possuem relação com o adoecimento mental.…”
Section: Introductionunclassified